2022
DOI: 10.3390/microorganisms10050874
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Microbiota Are Associated with Clinical Conditions That Extend beyond the Urinary Tract

Abstract: Background. Since the discovery of the human urinary microbiota (UM), alterations in microbial community composition have been associated with various genitourinary conditions. The aim of this exploratory study was to examine possible associations of UM with clinical conditions beyond the urinary tract and to test some of the conclusions from previous studies on UM. Methods. Catheterised urine samples from 87 men were collected prior to endoscopic urological interventions under anaesthesia. The composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
(62 reference statements)
0
5
0
2
Order By: Relevance
“…Lewis et al [ 25 ] showed that women with low levels of Lactobacillus are more commonly colonized with pathogens than those with diverse microbiota, which naturally decreases the risk of UTI development. However, changes in the natural microbiota of the urogenital system can be caused by many factors and are associated with age [ 26 ], medical treatment [ 7 ], diet, or diabetes [ 27 ]. Although there are many scientific reports on the antibacterial properties of Lactobacillus against pathogens, these data mainly concern strains isolated from the genital tract or food [ 8 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lewis et al [ 25 ] showed that women with low levels of Lactobacillus are more commonly colonized with pathogens than those with diverse microbiota, which naturally decreases the risk of UTI development. However, changes in the natural microbiota of the urogenital system can be caused by many factors and are associated with age [ 26 ], medical treatment [ 7 ], diet, or diabetes [ 27 ]. Although there are many scientific reports on the antibacterial properties of Lactobacillus against pathogens, these data mainly concern strains isolated from the genital tract or food [ 8 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the literature discussing the relationship between gut microbiota and bladder microbiota is limited. However, kidney function undoubtedly impacts the bladder microbiota, as evidenced by Hrbacek et al (2022), who found distinct overall microbial compositions between patients with CKD and healthy individuals . Furthermore, Kramer et al (2018) discovered that among patients with CKD, those with better kidney function (higher eGFR) exhibited greater diversity in their urinary microbiota .…”
Section: Strong Link Between Ckd and Gut Microbial Dysbiosismentioning
confidence: 99%
“…However, kidney function undoubtedly impacts the bladder microbiota, as evidenced by Hrbacek et al (2022), who found distinct overall microbial compositions between patients with CKD and healthy individuals. 22 Furthermore, Kramer et al (2018) discovered that among patients with CKD, those with better kidney function (higher eGFR) exhibited greater diversity in their urinary microbiota. 23 The composition of a patient's urine, which affects the urinary microbiota, can be influenced by kidney function.…”
Section: Strong Link Between Ckd and Gut Microbial Dysbiosismentioning
confidence: 99%
“…Major phylum of the bladder microbiota is Firmicutes (Table 1 ) [ 34 , 35 ]. Traditionally, the urinary environment was considered sterile; however, recent research has demonstrated the presence of a diverse microbial population in both healthy and diseases [ 154 , 155 ]. In 2011, Siddiqui et al [ 156 ] reported that the urinary microbiota in healthy women was predominantly composed to Lactobacillus species, similar to the vaginal microbiota, while women with urinary incontinence had a more diverse and less stable microbial community.…”
Section: Bladder Microbiotamentioning
confidence: 99%
“…These findings collectively suggest that disturbances in bladder function may contribute to mental health problems across different age groups, from children to elderly individuals. Given the emerging understanding of the role of bladder microbiota in bladder function [ 154 , 155 , 175 ], it is of great interest to investigate whether the bladder microbiota plays a role in both bladder function and psychiatric symptoms in patients with neuropsychiatric disorders. Further research in this area may provide valuable insights into the complex relationship between bladder function, neuropsychiatric disorders, and bladder microbiota.…”
Section: Bladder Microbiotamentioning
confidence: 99%